The The Effectiveness Of English Capacity Building In Developing Tourist Destination - Ritonga, Abdul Kadir; Muhammad Hamdani; Wirnawati br Sinaga (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Hotels are one of the mandatory accommodations. Optimal hotel management was a guide for every tourist to get comfort during their stay. This study aims to examine the performance of hotel managers in North Tapanuli regency through three variables: English capability, human resources development, and tourism destination.This study used a quantitative descriptive approach, with scoring and reduction data analysis techniques. The research samples were 50 hotel managers in North Tapanuli regency. Accidental sampling technique was used to select based on their categories. The sample was 50 respondents.The results showed English capacity building (X1) had a positive and significant effect on tourist destinations (X1) tcount 4.353 > ttable 2.01174 and a significant value of 4.353 > α 0.05, destination development (X2) had a positive and significant effect on tourist destination tcount 2,167 > ttable 1,992 and a significant value of 2,011 > α 0.05 and English capacity building (X1) and regional development (X2) simultaneously had a significant effect on tourist destinations (Y) that Fcount > Ftable or 26,285 > 3,200 and a significant level of 0.000 < 0.05. The research implications provide an overview of hotel performance in North Tapanuli as a reference in improving human resources development for hotel managers.